2020
DOI: 10.3389/fonc.2020.00060
|View full text |Cite
|
Sign up to set email alerts
|

miR-936 Suppresses Cell Proliferation, Invasion, and Drug Resistance of Laryngeal Squamous Cell Carcinoma and Targets GPR78

Abstract: MicroRNAs (miRs) play important roles in tumor progression. miR-936 has been reported to suppress cell invasion and proliferation of glioma and non-small cell lung cancer. Nevertheless, the function of miR-936 in laryngeal squamous cell carcinoma (LSCC) remains undiscovered. Hence, our study was to investigate the role of miR-936 in LSCC.In our present research, we have testified that miR-936 was substantially downregulated in LSCC tissues compared with adjacent normal tissues. Furthermore, miR-936 could inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 26 publications
1
30
0
Order By: Relevance
“…Recent studies have demonstrated that combination treatment with some miRNAs is able to reduce the chemoresistance of cancers. [35][36][37][38] Among these miRNAs, miR-140 is reported to function as a tumor suppressor. [24][25][26] Furthermore, previous studies have indicated that miR-140 can enhance chemosensitivity of some cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated that combination treatment with some miRNAs is able to reduce the chemoresistance of cancers. [35][36][37][38] Among these miRNAs, miR-140 is reported to function as a tumor suppressor. [24][25][26] Furthermore, previous studies have indicated that miR-140 can enhance chemosensitivity of some cancers.…”
Section: Discussionmentioning
confidence: 99%
“…This finding suggested that miR-503-5p may play an unknown role in the effect of tobacco on SCCHN. In general, miRNAs exert diverse regulatory roles through target differential mRNAs [11,14,16,22,40], same for miR-223-3p and miR-204-5p. Considering the potential clinical significance of miR-223-3p and miR-204-5p, it is necessary and worthy to define the possible targets for providing reference for the followed study.…”
Section: Discussionmentioning
confidence: 99%
“…13 However, the recurrence, metastasis, and insensitivity to radiotherapy or chemoresistance often lead to poor therapeutic effects for LSCC, which cannot be solved by traditional therapies. 14,15 Therefore, it is urgent to identify novel targets for the treatment of LSCC. In the present study, we demonstrated that USP34 promoted LSCC cell survival and drug resistance by stabilizing SOX2, and targeting USP34/SOX2 axis may be a promising strategy to combat LSCC.…”
Section: Discussionmentioning
confidence: 99%